UTILIZING CANVA-BASED LEARNING VIDEOS TO INCREASE STUDENTS' INTEREST IN LEARNING ON PRE HISTORIC MATERIALS AT SMPN 4 MEUKEK ACEH SELATAN DISTRICT - Resijan; Siti Mayang Sari; Akmaluddin; Syarfuni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In increasing student interest in learning in the teaching and learning process,it can be done in various ways, one of which is by using and utilizing the resultsof technology. One of the results of technology that is interesting and effectiveand easy to use is to use learning videos through the Canva application. Theresearch method in writing this research uses an approach, namely a qualitativedescriptive approach. The purpose of the study is to determine the use oflearning videos using Canva to increase students' interest in prehistoricmaterial. Video learning is a strategy or learning method to deliver content ormaterial using video media in the teaching and learning process. Canva is anapplication that is present in the crowded world of technology. This applicationis an online design program that provides a variety of tools includingpresentations, resumes, posters, pamphlets, brochures, graphics, infographics,banners, and other types available in the Canva application. Student interest inpre-historic material can be increased by utilizing learning videos. A cleardisplay and attractive visuals in learning videos will overcome boredom anddislike for complex material. The use of Canva as a tool to create learningvideos has been effective in increasing student interest in learning. The app'sease of use, with a large selection of templates and attractive design elements,can help teachers create engaging and high-quality learning content.